Learning about my body: viva education: science works for kids series - Moore, Jo Ellen (Viva Education New Delhi, 2004)
This book focuses on personal health and body awareness, teaching children about their own bodies and the importance of self-care. It covers topics like hygiene, nutrition, and physical activity in a fun and relatable way, helping kids understand how to take care of themselves.